Homogenization of Stationary Navier-Stokes Equations in Domains with 3 Kinds of Typical Holes (Journal of Partial Differential Equations, 2021)
"The aim of this paper is to investigate homogenization of stationary Navier-Stokes equations with a Dirichlet boundary condition in domains with 3 kinds of typical holes. For space dimension $N$ =2 and 3, we utilize a unified approach for 3 kinds of tiny holes to accomplish the homogenization of stationary Navier-Stokes equations. The unified approach due to Lu [1] is mainly based on the uniform estimates with respect to \u03b5 for the generalized cell problem inspired by Tartar."